Intra- and inter-observer concordance of the stabilizing chains test and its relationships with measures on a force platform - Vázquez, Orlando Conde; Fernández, Carlos Mohíno (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: There are numerous manual tests that are part of the daily work of clinicians, in order to assist in the diagnosis to a subsequent therapeutic approach. Objectives: The stabilizing chains* test was chosen to study its intra- and inter-observer reproducibility in 24 children with 11 years old, and the possible relation with certain baropodometric variables. Methods: The test data were collected by 2 operators and the baropodometric variables by a force platform. Cohen’s Kappa coefficient and Student’s t-tests were performed. Results: The results showed a good kappa coefficient (0.497 - 0.746) in the intra-observer and poor to moderate in the inter-observer (0.083 - 0.438). There are also relationships to the weight percentage in the frontal and sagittal planes (p ≤ 0.05). Conclusion: These results give validity to use the test in daily practice. * The English denomination of the test is a literal translation of the French expression ‘chaînes stabilisatrices’.